Borrelia recurrentis in Head Lice, Ethiopia - Amina Boutellis; Oleg Mediannikov; Kassahun Desalegn Bilcha; Jemal Ali; Dayana Campelo; Stephen C. Barker; Didier Raoult (Emerging Infectious Diseases, 2013)
Since the 1800s, the only known vector of Borrelia recurrentis has been the body louse. In 2011, we found B. recurrentis DNA in 23% of head lice from patients with louse-borne relapsing fever in Ethiopia. Whether head lice can transmit these bacteria from one person to another remains to be determined.